SOCIAL CHANGE IN MUSLIM TEENAGERS AT THE ERA OF GLOBALIZATION; THEORETICAL AND PRACTICAL STUDIES - Bashori, Moh Hasan; Hidayat, Fajar (Mozaic: Islamic Studies Journal, 2023)
The social changes that have occurred have resulted in many teenagers perhaps lacking the ability to fully understand the use of refined Javanese (kromo inggil). In addition, there has been a change in fashion, with many students no longer wearing batik as the kiblat and lacking the confidence to wear traditional Indonesian batik. Due to their tendency to imitate Western culture that many students see as the kiblat. a large number of young people have lost sight of their national identity as Indonesians and as a result Indonesian culture may be gradually forgotten. The purpose of this study is to explain how, in the era of globalization, social change occurs in teenagers. This shift is the result of the influence of Western culture that penetrates Indonesian teenage society through social media and influences interaction patterns, language styles, fashion changes, and other areas. This study uses a descriptive qualitative research design. This study shows that there is a change in the way teenagers interact with each other, including in terms of communication and language